Seroprevalence and associated risk factors of brucellosis in buffaloes in district Layyah - Kashif, Muhammad; Nasir, Amar; Ullah, Samee; Tunio, Muhammad Tarique; Sikandar, Arbab; Rizwan, Muhammad; Asif, Muhammad; Abbas, Mazhar (Buffalo Bulletin, 2024)
Brucellosis causes huge economic losses in the dairy industry and highly contagious and zoonotic disease lead to infertility, decreased overall milk production, and abortion in dairy animals. The aim of this study was to find the seroprevalence and associated risk factors of brucellosis in different breads of buffalo in District Layyah. For this purpose, Rose Bengal Plate Test (RBPT) and Milk Ring Test (MRT) were performed using the standard procedure. The results showed that the higher prevalence of brucellosis was found (6.6%) in tehsil Layyah compares to the other tehsils. The overall prevalence in the District Layyah was found 4.7% and Nilliravi bread was found more susceptible than the Kundi breed. The animals older than 5 years were found to be more susceptible as compared with younger animal. The prevalence of brucellosis was more in female buffaloes.as compared with the male. There was more abortion and reduction in milk in seropositive animals. It was concluded that higher prevalence of brucellosis in buffaloes and higher authorities should take measures to eliminate the seropositive animals to prevent the spread in people who are directly engaged with these animals’ veterinary staff and farmers.